Prevalence and Risk Factors of Urinary Tract Infections in Hospitals in Yogyakarta - Kusbaryanto, Kusbaryanto; Gobel, Fatmah Afrianty; Listiowati, Ekorini; Rosyida, Aisyah (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2024)
Urinary tract infection is an infectious disease that is common in society and brings many disadvantages, including longer treatment and more expensive treatment costs. This study aimed to analyze the prevalence and risk factors for Urinary Tract Infections (UTI) at Hospital, Yogyakarta. The research design is an analytical observational study using a cross-sectional design. The samples in this study were patients diagnosed with Urinary Tract Infection at the hospital. Sample selection method Sampling was carried out by consecutive sampling. Retrieval of data from patient data stored in medical records. Ethics permit from PKU Muhammadiyah Gamping Hospital with number: 053/KEP-PKU/III/2023. The prevalence of UTI during the 2 years of data collection was 65 people, with details of 16 men and 49 women. There is a relationship between length of stay and the incidence of UTI with p = 0.019 and OR = 2.56, there is a relationship between age and UTI with p = 0.001 and OR = 7.113 and there is a relationship between gender and UTI with p = 0.001 and OR = 4,136. The effect of length of treatment, age, and gender on the incidence of UTI was 31.4%. The incidence of UTI was 65 cases. Factors that influence the incidence of UTI are length of stay, age, and gender with a p-value of 31.4%. The study concluded that length of stay, age, and gender significantly influence the incidence of Urinary Tract Infections at Hospital, Yogyakarta, with these factors accounting for 31.4% of the variance in UTI cases.